The global trade environment in the Biden era and response strategies for Korea - Yeongkwan Song (Korea Development Institute (KDI), 2021)
Many expect that the trade war between the US and China will persist, and East Asia's global value chains will undergo a significant transformation in the mid- to long-term, as China's contracts while that of ASEAN expands. Accordingly, to effectively respond to the coming changes, Korea should adopt proactive strategies to join the Comprehensive and Progressive Agreement for Trans-Pacific Partnership (CPTPP), and attract quality FDI in an effort to realize sustainable growth.
Keywords: 330